Study Of Transport Reform And Development In The Middle Of The Covid-19 Pandemic In Sidoarjo Regency - Dadang Supriyatno; Sri Wiwoho Mudjanarko; Satriana Fitri Mustika Sari (LPPM of NAROTAMA UNIVERSITY, 2022)
Sidoarjo is part of the Gerbangkertosusila which is a Metropolitan area, so facilities and infrastructure are needed that are able to support the needs of the city together with the Covid-19 pandemic, it is necessary to revitalize fundamental public transport. According to a survey conducted using the AHP method, the model Y= 0.158X1 + 0.187X2 + 0.135X3 + 0.156X4 + 0.126X5 + 0.131X6 + 0.066X7 + 0.042X8. The calculation results show that the city of Sidoarjo is ready to be developed. The development carried out is to develop the existing transportation route Purabaya Terminal - Porong Terminal into road-based mass transportation, namely medium buses with a capacity of 30 passengers, which has a circulation time of 1 hour 49.25 minutes/trip, with a load factor of 77%, headway 11.55 minutes , and a fleet that requires 12 units of the fleet, as well as the temporary tariff determined according to the BOK of Rp. 8.334,-. The revitalization of existing transportation is by scraping by rerouting existing transportation to be used as feeders, rejuvenating existing transportation, selling it outside the city, and if it is not roadworthy, old iron scrap is sold using the kiloan method